Examining the influence of personal-time-based accessibility on the frequency of public transit use among older adults across Canada - Meredith Alousi-Jones; Ahmed El-Geneidy (Transportation Research Interdisciplinary Perspectives)
Many older adults face the prospect of driving cessation as they age. Ensuring that public transit services meet their needs could contribute to their independent mobility and long-term health. Accessibility, the ease of reaching destinations by a certain mode, is a measure that can be used to indicate how well the land use and transport systems allow people to reach their desired destinations. This paper explores how perceived and objective levels of accessibility influence older adults’ frequency of public transit use in a Canadian context. Based on a survey collected in six Canadian regions (N = 2,452), we use respondents’ stated reasonable travel time by public transit to generate a personal-time-based cumulative accessibility measure. We then develop a weighted binary logistic regression model to understand the impacts of the personal-time-based accessibility measure, perceived accessibility, and other personal characteristics on older adults’ frequency of public transit use. The results indicate that both perceived and personal-time-based accessibility have a strong and positive impact on frequent public transit use. Older women were found to be more frequent public transit users, whereas older adults who have access to a private vehicle use public transit significantly less. Findings from this research support the utilization of accessibility by public transit as a tool to better assess and plan for the transport needs of older adults. The results can be relevant for transport planners and policy makers interested in improving the well-being and independence of older adults through increasing their use of public transit.